Smartbox Media for Fraction Concept Understanding in Elementary Students: Smartbox Media untuk Memahami Konsep Pecahan pada Siswa Sekolah Dasar - Nia Laily Rahmawati; Mahardika Darmawan Kusuma Wardana (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Mathematics is a structured discipline essential for developing logical and critical thinking skills in elementary education. Specific Background: Fraction topics are often perceived as difficult due to their abstract nature and limited use of concrete learning media. Knowledge Gap: There is limited application of interactive and technology-supported manipulatives, such as Smartbox, to facilitate fraction learning in an engaging and meaningful way. Aims: This study aims to develop and examine the use of Fraction Smartbox as an interactive learning medium to support students’ understanding of fraction concepts. Results: The developed Smartbox integrates manipulative materials with simple technological features such as light and sound indicators, enabling students to receive immediate feedback on their answers and engage actively in learning activities. Novelty: The study introduces Smartbox as a concrete and interactive instructional medium combining physical and technological elements for fraction learning. Implications: The findings suggest that the use of Smartbox provides an engaging and meaningful learning experience, supporting students in understanding abstract fraction concepts through interactive and contextual approaches. Keywords: Smartbox, Fraction, Learning Media, Elementary Education, Interactive Learning Key Findings Highlights Interactive features provide direct feedback during learning activities Concrete representation supports conceptual comprehension of fractions Learning activities become more engaging and meaningful